2020
DOI: 10.1371/journal.pone.0230408
|View full text |Cite
|
Sign up to set email alerts
|

“Chasing the pain relief, not the high”: Experiences managing pain after opioid reductions among patients with HIV and a history of substance use

Abstract: Background Opioid overdose mortality continues to increase in the United States despite significant investments to reverse the epidemic. The national response to-date has focused primarily on reducing opioid prescribing, yet reductions in prescribing have been associated with patients reporting uncontrolled pain, psychological distress, and transition to illicit substances. The aim of this study is to qualitatively explore chronic pain management experiences among PLWH with a history of illicit substance use a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…46,47 Despite a lack of evidence supporting long-term opioid efficacy in CNCP treatment and some evidence suggesting improved pain scores with opioid tapering, 48,49 recent studies have cited potential harms of opioid discontinuations, including increased suicidal ideation from uncontrolled pain, return or initiation of illicit drug use leading to increased overdose risk and death, and increased emergency department visits and hospitalizations from adverse health events. [50][51][52][53][54][55][56] While we do not know whether participants consented to opioid discontinuations, mounting pressure from regulators to curb opioid prescriptions suggests many were likely provider-directed. 18,21,24,45 Even as discontinuations likely had justifications in prioritizing safety, our finding highlights the need for providers and policy makers to further examine the potential negative impacts of opioid prescribing policy changes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…46,47 Despite a lack of evidence supporting long-term opioid efficacy in CNCP treatment and some evidence suggesting improved pain scores with opioid tapering, 48,49 recent studies have cited potential harms of opioid discontinuations, including increased suicidal ideation from uncontrolled pain, return or initiation of illicit drug use leading to increased overdose risk and death, and increased emergency department visits and hospitalizations from adverse health events. [50][51][52][53][54][55][56] While we do not know whether participants consented to opioid discontinuations, mounting pressure from regulators to curb opioid prescriptions suggests many were likely provider-directed. 18,21,24,45 Even as discontinuations likely had justifications in prioritizing safety, our finding highlights the need for providers and policy makers to further examine the potential negative impacts of opioid prescribing policy changes.…”
Section: Discussionmentioning
confidence: 98%
“…Prior studies exploring pain management in this population have, in fact, reported effectiveness of multimodal pain treatments in managing pain, suggesting these services may offer benefit if made more available to patients. 6,7,56 Studies show HIV providers operate within the "HIV paradigm," prioritizing patient engagement, care retention, adherence to therapy, and viral suppression. 69,70 This paradigm may conflict with conservative opioid prescribing guidelines, and HIV providers may be more likely to continue opioid prescriptions or tolerate problematic substance use out of concern that opioid discontinuation may reduce care retention and worsen HIV outcomes.…”
Section: Continuedmentioning
confidence: 99%
“…Inadequately managed pain and denial of pain drug treatments have been identified as risk factors for illicit drug use, particularly among people with history of substance use. 29 43 44 The Canadian Pain Task Force has identified a need to foster shared decision making between providers and individuals living with chronic pain and “support opioid prescribing that balances the benefits and harms of these medications based on the needs of the individual.” 45 Improved access to multidisciplinary approaches to treat pain is also needed. 14 45 Regarding non-opioid interventions, evidence suggests that some non-invasive (eg, exercise therapy, multidisciplinary rehabilitation, cognitive behavioural therapy) and invasive (eg, nerve blocks) treatments can improve function and/or reduce pain for specific conditions.…”
Section: Discussionmentioning
confidence: 99%
“…While non‐opioid treatments are available for pain, given the intensity of pain experienced by PLHIV, opioids, both from regulated and unregulated sources, are commonly used analgesics among PLHIV [12,13]. Furthermore, given the often chronic nature of their pain, long‐term opioid therapy is common among PLHIV [12].…”
Section: Introductionmentioning
confidence: 99%
“…Given the rise in opioid‐related overdoses across the USA and Canada, policy interventions, including revised clinical practice guidelines, focused on reducing opioid prescribing have been introduced in recent years [20,21]. Unfortunately, this has resulted in untreated pain for many individuals with chronic and serious illness as they are now unable to obtain or fill opioid prescriptions, or have had their opioid dose abruptly lowered or discontinued [13,22,23]. Lack of access to adequate pain relief has forced more individuals to self‐medicate and turn to drugs from an unregulated and increasingly fentanyl‐adulterated illicit drug market, raising concerns of increased overdoses and exposure to other drug‐related harms [13,22,23].…”
Section: Introductionmentioning
confidence: 99%